2006
DOI: 10.1007/s11630-006-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

3D computation of hydrogen-fueled combustion around turbine blade-effect of arrangement of injector holes-

Abstract: Recently, a number of environmental problems caused from fossil fuel combustion have been focused on. In addition, with the eventual depletion of fossil energy resources, hydrogen gas is expected to be an alternative energy resource in the near future. It is characterized by high energy per unit weight, high reaction rate, wide range of flammability and the low emission property. On the other hand, many researches have been underway in several countries to improve a propulsion system for an advanced aircraft. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The diameter of the injector hole is 3.0(mm) and the pitch of the holes is 3.0mm. This layout of injector holes has the highest feasibility among 5 cases studied in the previous study [5].…”
Section: Flow Conditionsmentioning
confidence: 83%
See 1 more Smart Citation
“…The diameter of the injector hole is 3.0(mm) and the pitch of the holes is 3.0mm. This layout of injector holes has the highest feasibility among 5 cases studied in the previous study [5].…”
Section: Flow Conditionsmentioning
confidence: 83%
“…They concluded that this concept has the highest possibility by employing the hydrogen injection rate of 2H 2 /O 2 =0.25. Yamamoto et al [5] studied the interaction between the secondary flow and the endwall in a linear vane cascade. They found that the surface temperature on the endwall becomes extremely high (about 3000K) because of the secondary flow pattern.…”
Section: Introductionmentioning
confidence: 99%